CHANGE MANAGEMENT FOR ENSURING EFFECTIVE DEVELOPMENT OF THE ENTERPRISE UNDER CRISIS EVENTS - NATALIA, Smolinska; LISKEVYCH, Sofiia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In the context of contemporary globalization challenges and economic instability, enterprises are confronted with an urgent need to enhance their management strategies to ensure sustainable development amidst crisis situations. Crisis events such as economic downturns, natural disasters, political instability, and global pandemics pose significant challenges to businesses, necessitating immediate response and adaptation of management strategies.This research aims to study and develop effective approaches to change management in crisis situations to ensure sustainable enterprise development. The relevance of the topic is driven by the necessity for a deep analysis of problems and the development of practical recommendations for enterprises to successfully adapt to changing conditions.The study conducts a comprehensive analysis of scientific sources reflecting current trends in change management and crisis situations. It focuses extensively on studying adaptive management strategies, including changes in strategic planning, operational management, financial management, and human resources management. The paper examines in detail the key impacts of crisis situations on enterprise operations and proposes specific tools for effectively managing these challenges.Particular attention is given to identifying critical success factors in crisis management, including organizational flexibility, innovation in problem-solving, rapid response capability, and adaptation to new conditions. Based on the analysis of scientific literature and practical experience, recommendations are developed for enterprise management to optimize change management strategies during crises.The main findings of the study include the development of a strategic change management model aimed at ensuring resilience and competitiveness of enterprises in crisis conditions. This model considers the specific impacts of crisis phenomena on various functional areas of business and recommends a comprehensive approach to change management, encompassing strategic planning, risk management, communication strategies, and personnel support.
Keywords: change; change management; development; crisis phenomena; enterprise development management